Socio-cultural analysis on a textbook Grow with English for students of elementary schools - yuli yana wati; Ikariya Sugesti (Concept : Community Concern for English Pedagogy and Teaching, 2022)
Indonesian culture is often connected with the reality of life and it appears on textbook Grow with English. This research aims to analyze the representation of Indonesian culture on Grow with English textbook for third grade of elementary school. The problems of the research are the teacher only focuses on theory or language itself, without recognizing another aspect inside the textbook that is socio-cultural aspect. Students have difficultly to know Indonesian culture that appears on the English textbook. This research was descriptive qualitative by which the researcher interprets of Indonesian culture in the data of word and description from picture. The findings showed that there were various illustrations that indicated Indonesian culture, the characters’ name indicated of origin, traditional attribute that indicated of religion, traditional home living, traditional food, traditional toys and game, the last about physical appearance of the character and it is indicated socio-cultural aspect. Furthermore, for teachers who are interested in doing similar research, this research will be reference, it is appropriate English textbook for elementary school and as contribution to comprehend that Indonesian culture appears on Grow with English textbook and recommended to use it continually. Keywords: socio-cultural; textbook; students of elementary school